2004
DOI: 10.2337/diacare.27.10.2335
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hyperglycemia Alters Mood State and Impairs Cognitive Performance in People With Type 2 Diabetes

Abstract: OBJECTIVE -To examine the effects of acute hyperglycemia on cognitive function and mood in people with type 2 diabetes.RESEARCH DESIGN AND METHODS -Twenty subjects with type 2 diabetes, median age 61.5 years (range 53.1-72.0), known duration of diabetes 5.9 years (range 2.8 -11.2), BMI 29.8 kg/m 2 (range 22.0 -34.6), and HbA 1c 7.5% (range 6.7-8.4) were studied. Treatment modalities varied from antidiabetic medications to insulin. A hyperinsulinemic glucose clamp was used to maintain arterialized blood glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
155
4
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(179 citation statements)
references
References 26 publications
16
155
4
4
Order By: Relevance
“…Comparable cognitive performance decrements, including executive function, but a lack of change in other cognitive domains such as sustained attention and immediate verbal recall were observed in this study following the high-vs low-GI carbohydrate meal compared with the decrements reported by Sommerfield and colleagues, where similar levels of blood glucose were attained using a hyperglycaemic/hyperinsulinaemic clamp [5]. Collectively, these results support an argument that more robust hyperglycaemia-induced decrements are apparent in more complex tasks [5].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Comparable cognitive performance decrements, including executive function, but a lack of change in other cognitive domains such as sustained attention and immediate verbal recall were observed in this study following the high-vs low-GI carbohydrate meal compared with the decrements reported by Sommerfield and colleagues, where similar levels of blood glucose were attained using a hyperglycaemic/hyperinsulinaemic clamp [5]. Collectively, these results support an argument that more robust hyperglycaemia-induced decrements are apparent in more complex tasks [5].…”
Section: Discussionsupporting
confidence: 79%
“…Increasingly evident is that transient periods of hyperglycaemia may be detrimental to cognitive performance in [4][5][6], with this study demonstrating that meal-induced changes in blood glucose are of sufficient magnitude to affect performance adversely. Admittedly, performance following pasta or bread consumption, compared with performance on water days, did not provide a consistent pattern of benefit following pasta consumption and decrement following bread intake.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This hyperglycaemia would also cause an acute confusional state and significantly accelerate their cognitive decline. 22 Loss of continence with hyperglycaemia should also be considered in these patients because it contributes to their risk of falls and infection. Weight loss in the face of reasonable food intake should also alert physicians to consider poor glycaemic control in such patients.…”
Section: Effects Of Diabetes On Dementiamentioning
confidence: 99%
“…Additionally, quick or slow administration of drug affects the pain. Recommended administration time for 1 ml drug is 10 seconds [5][6][7][8][9][10]. Quick administration of drug increases the level of pain.…”
Section: Introductionmentioning
confidence: 99%